2005
DOI: 10.1021/bi051207d
|View full text |Cite
|
Sign up to set email alerts
|

Mutations at Leucine 215 of β-Tubulin Affect Paclitaxel Sensitivity by Two Distinct Mechanisms

Abstract: Paclitaxel resistance mutations in Chinese hamster ovary cells frequently alter a cluster of leucine residues in the H6-H7 loop region of beta-tubulin. To gain further insight into the role of this region in microtubule assembly and drug resistance, site-directed mutagenesis was used to systematically change amino acid L215. The mutated genes were cloned into a tetracycline-regulated expression vector and transfected into wild-type cells. Most of the mutations destabilized microtubule assembly, causing a decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Furthermore, only recently, L215I substitution has been evidenced to enhance the binding or effectiveness of paclitaxel by affecting H6-H7 loop of beta-tubulin in microtubule assembly. 28 In the present study, a non tumorigenic breast cell line and 3 breast cancer cell lines with different sensitivity to paclitaxel and already deeply biologically characterized in our laboratory, 29 have been used. Missense mutations occurred only in MCF-7 and SK-BR-3 cell lines and the presence of mutations in the same regions of tumor cell lines with different paclitaxel-chemosensitivity suggested that tubulin alterations could be unrelated to the drug response.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, only recently, L215I substitution has been evidenced to enhance the binding or effectiveness of paclitaxel by affecting H6-H7 loop of beta-tubulin in microtubule assembly. 28 In the present study, a non tumorigenic breast cell line and 3 breast cancer cell lines with different sensitivity to paclitaxel and already deeply biologically characterized in our laboratory, 29 have been used. Missense mutations occurred only in MCF-7 and SK-BR-3 cell lines and the presence of mutations in the same regions of tumor cell lines with different paclitaxel-chemosensitivity suggested that tubulin alterations could be unrelated to the drug response.…”
Section: Discussionmentioning
confidence: 99%
“…These mutations seem to act by altering the assembly of microtubules (25). More recent studies have further shown that an L215I mutation in h-tubulin increases sensitivity to paclitaxel, most likely by increasing the binding affinity for the drug (37). Thus, a variety of structural, biochemical, and genetic studies have identified this region as having important significance in microtubule assembly, drug action, and drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…41 Drug development has focused on new drugs that are resistant to the function of this transporter, 42 and perhaps synthesis of MCAK inhibitors would alleviate this problem. In vitro studies have also found that mutations in tubulin subunits cause cell lines to have conferred a resistance to paclitaxel 43,44 and vinblastine. 45,46 MCAK may function at a site distinct from paclitaxel and vinblastine on the MT, and so its inhibitory effects may not be altered by these mutations, an idea that remains to be tested in the laboratory.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%